Struktur Kepemilikan Institusional, Koneksi Politik dan Kebijakan Dividen Perusahaan di Bursa Efek Indonesia - Novia Nursyahbandarmahdi; Siti Sarah; Luciana Haryono (Studi Akuntansi dan Keuangan Indonesia, 2020)
The purpose of this study was to determine whether institutional ownership, political connections, and institutional ownership on political connected companies affects the dividend policy of Indonesian companies listed on the Indonesian Stock Exchange from 2012 - 2017. The sample used in this study were totaled to 255 non-financial companies in Indonesia with total observations of 1530. The model used on this study was the Tobit regression model. The results show that institutional ownership has the tendency to not pay dividends, whereas political connections on companies tends to support the payment of dividends to the shareholders. Furthermore, this study found that when there is the presence of interactions between political connections and institutional ownership in the company, political connections tends to have a positive impact towards dividend policy, yet institutional ownership has an increasingly significant negative effect on dividend policy.